Activation of raphe efferents to the medial prefrontal cortex by CRF; correlation with anxiety-like behavior - Meloni, Edward G. (2007)
BACKGROUND: Parallel lines of research suggest that dysfunction affecting both corticotropin-releasing factor (CRF) and serotonin (5-HT) systems is involved in the pathophysiology of psychiatric illnesses such as anxiety and depression. The effect of CRF on behavior, and on the accompanying change in activity of 5-HT neurons in the dorsal and median raphe nuclei (DR and MR) that project to the ventral medial prefrontal cortex (mPFC), a brain area implicated in mood and anxiety disorders, was studied. METHODS: Male Sprague-Dawley rats with intra-mPFC deposits of fluorescent microspheres received injections of CRF (1 μg, icv) and were tested for CRF-enhanced startle, a behavioral assay believed to reflect stress- or anxiety-like states. C-Fos immunohistochemistry was used to measure CRF-induced activity in retrogradely-labeled neurons in the DR and MR and correlate this level of activity with the level of CRF-enhanced startle. RESULTS: CRF-enhanced startle was accompanied by an increase c-Fos expression in retrogradely-labeled cells in the raphe. In the DR and MR, there was a clear topography of activation, with a higher percent activation in retrogradely-labeled neurons in caudal sections. In the caudal DR, this effect was positively correlated with the level of CRF-enhanced startle. Coexpression of retrogradely-labeled cells with tryptophan hydroxylase showed that the majority (> 90%) of raphe efferents to the mPFC were from serotonergic neurons. CONCLUSIONS: These data indicate that CRF activates a subpopulation of cortical-projecting 5-HT raphe neurons, and suggest that increased 5-HT release in the mPFC may be an important component driving some types of anxiety-like behaviors.